في تنمية الصور الذهنية لدى الطفل الاصم المستفيد من الزرع القوقعي Pictogrammes فعالية بطاقات التخاطب - ساسان إلهام (University of Eloued جامعة الوادي, 2024)
Abstract: The current study aimed to know the effect of Pictograms on the mental image of the deaf child and the aspects that develop it. In our study, we relied on a sample of 03 children who benefited from a cochlear implant device. She picked up from Dorban El Jisr El Abyad Hospital in Annaba. In addition, we used the most important tools, which are as follows: observation, the application of the PECS program to develop the mental image and the application of the MAT test to assess the effectiveness of speech cards in developing the mental image using the naming and assignment clause. Our study revealed that deaf children benefiting from cochlear implants who follow the Pictograms program have a mental image that enables them to memorize, retrieve and communicate well. على تنمية الصورة الذهنية للطفل الأصم، اعتمدت الدراسة على عينة تتكون من 03 أطفال مستفيدين من جهاز الزرع القوقعي، تتراوح أعمارهم ما بين خمسة سنوات وخمس سنوات ونصف، تم انتقائها من مستشفى ضربان يتمتع بصورة ذهنية تمكنه من الحفظ والاسترجاع والتواصل الجيد. Pictogrammes لتقييم مدى فاعلية بطاقات التخاطب في تنمية الصورة الذهنية من خلال استخدام بند التسمية والتعيين. اسفرت الدراسة إلى أن الطفل الاصم المستفيد من جهاز الزرع القوقعي المتتبع لبرنامج بطاقات التخاطب MAT لتنمية الصورة الذهنية، اختبار PECS الجسر الأبيض لولاية عنابة، كما استعملت الادوات التالية في جمع، تحليل وتفسير النتائج: برنامج Pictogrammes ملخص: هدفت الدراسة الحالية الى معرفة فعالية بطاقات التخاطب
دراسة ميدانية بمستشفى الحكيم ضربان عنابة
Keywords: بطاقات تخاطب; زرع قوقعي; صورة ذهنية; طفل أصم; Speech cards; mental image; cochlear implant; deaf child